Design of High performance and Low power Simultaneous Multi-Threaded Processor - Krishan Arora; Paramveer Singh Gill; Parul Mehra (Institute of Advanced Engineering and Science, 2013)
In this paper, we present the design of a High Performance Multi-Threaded Processor. Processing of high quality images is inevitable in applications such as, HD TV, Gaming Multimedia, etc. which require a great processing power with low power consumption. This can be achived with multi-threaded processors which optimally utilises the Functional Units (Fus). The speed of processing is as good as multi-core processors with lesser area. A conflict resolver (CR) is designed for scheduling the instructions, which involves allocation of Fu. The data move instructions are in majority in any of the programs; the corresponding logic blocks are replicated and speed of execution is further improved. We illustrated for two-threaded processorHowever, it is possible to extend the design for any number of threads by suitably redesigning the CR, and also replicate Transfer Logic and CPU Registers.DOI:http://dx.doi.org/10.11591/ijece.v3i3.2530